Biology of the mealybug, Phenacoccus solenopsis Tinsley (Pseudococcidae: Hemiptera) on sprouted potato and brinjal plant (The Journal of Plant Protection Sciences, 2022)
The biology of the mealy bug, Phenacoccus solenopsis Tinsley was studied on brinjal plant and sprouted potato tubers in  the laboratory. The female nymphs moulted three times for becoming adults while the male took four moultings. The  female and male nymphs completed development in 14.45 ± 0.96 days and 19.53±1 days respectively on brinjal plant at   0 20-36.2 C temperature and 15.1±1 days and 18±0.82 days respectively on sprouted potato. The ratio of the male: female were 1:1.75 and 1:1.87. The duration from nymphs to adult female was 28 days on brinjal plant and 25 days on sprouted potato tubers. The pre-oviposition period was 6.37 ± 1.29 days and 6.89±0.84 days on brinjal and sprouted potato respectively. The average oviposition period was 5.89±0.89 days and 7.5±0.52 days on brinjal plant and sprouted potato tubers. Fecundity rate was 205-278 eggs/female.
Keywords: Biology; Fecundity; Moulting; Phenacoccus solenopsis